Гейміфікація як інструмент навчання іноземної мови у закладах вищої освіти - Супрун, Олена Миколаївна; Супрун, Елена Николаевна; Suprun, Olena (ТДАТУ, 2021)
The article considers the prospects of introducing gamification into the educational process while teaching foreign languages in higher education institutions. The main components of the gamification process and elements of its implementation are looked into, the positive factors of using the principles of gamification for enhancing e-learning and the independent work of students in the context of distance and blended learning are described. An overview of resources for gamification of the educational process is provided.
Keywords: gamification; e-learning; interactive methods of teaching; game mechanics; teaching ESP; enhancing learning; motivation